Francesco Ruffini dagli ideali del Risorgimento al regime fascista: Un itinerario culturale - Varnier, Giovanni Battista (La pena nei diritti delle religioni, 2019)
The essay deals with a review of some recent publications about Francesco Ruffini, (Lessolo, 10th April 1863 – Torino, 29th March 1934), one of the most prominent scholars in the field of the new Italian system of law and religion during the late 19th and early 20th Century.